FRI0011 IL-10-Producing Regulatory B Cells are Decreased in Systemic Sclerosis. (9th June 2015) - Mavropoulos, A.; Simopoulou, T.; Varna, A.; Liaskos, C.; Katsiari, C.; Bogdanos, D.; Sakkas, L.
Abstract : Background: Systemic sclerosis (SSc) is a characterized by extensive fibrosis and a plethora of autoantibodies, the latter being indicative of breakage of tolerance. Regulatory B cells (Bregs) producing interleukin (IL)-10 play a significant role in suppressing inflammatory immune responses and preventing autoimmunity Objectives: To investigate the significance of IL-10-producing Bregs in SSc Methods: The study groups consisted of 45 patients with SSc (12 with early SSc, 33 with established SSc [of whom 16 with SSc-associated lung fibrosis, SSc-LF]) and 10 healthy controls (HCs). As a disease controls for SSc-LF, 12 patients with rheumatoid arthritis-associated LF (RA-LF) were included. Peripheral blood monunuclear cells were isolated from patients and controls. Phenotypic analysis of immature/transitional Bregs (CD19+CD24highCD38high) and memory Bregs (Cd19+CD27+Cd24high) was carried out by flow cytometry using FACS Calibur. The function of bregs was evaluated by IL-10 expression after Bcell culture with toll-like receptor (TLR)9 stimulation, and flow cytometry analysis Results: Memory Bregs were decreased in early SSc (1.85±0.38), established SSc (1.6±0.88), and SSc-LF (1.52±0.17) compared to HCs (6.3±0.49, p<0.001). There were more decreased in diffuse cutaneous SSc (dcSSc) than limited cutaneous SSc (lcSSc), but not significantly so. The lowest percentage of memory Bregs was in dcSSc-LF (1.36±0.16). Memory Bregs were also numerically decreased in RA-LF compared to HCs (1.58±0.26, p<0.001). Transitional Bregs were also numerically decreased in early SSc, and established SSc compared to HCs (p<0.02). Bregs IL-10 expression after Toll-like receptor (TLR)-9 stimulation (innate stimulus) was impaired in SSc, particularly in SSc-LF. Conclusions: This is the first study to demonstrate that Bregs are reduced and functionally impaired in SSc, particularly SSc-LF. The impaired IL-10 production after innate stimulus may have clinical implications. The impairment of Bregs along with the reported increased expression of the stimulatory Bcell receptor CD19 in SSc support B cell autoaggression in SSc. These findings may offer a new therapeutic strategy for SSc, namely expanding Bregs ex-vivo and re-administering them to patients with SSc. Disclosure of Interest: None declared